Inclusive Development and the Islamic Economic Paradigm: Unveiling Structural and Epistemic Injustices in Indonesia - Anindya Aryu Inayati; Agung Barok Pratama; Andhita Risko Faristiana; Richa Angkita Mulyawisdawati (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2025)
Inclusive economic development is a constitutional mandate aimed at achieving economic democracy, social justice, and public welfare. However, these goals are often hindered by structural barriers and dominant perspectives that marginalize vulnerable groups. This article analyzes how structural and epistemic injustices shape inclusive development in Indonesia through the lens of the Islamic economic paradigm. Using a qualitative-descriptive approach grounded in policy documents, legal texts, and critical literature, this study employs thematic analysis. The findings show that development policies tend to prioritize elite capital accumulation and large-scale projects, while neglecting the voices and local knowledge of marginalized communities. By integrating the ethical values of ‘adl, maṣlaḥah, and ta‘āwun, with epistemological critique, this article argues that genuine inclusivity requires not only institutional reform or Islamic philanthropy, but also participatory governance and the rethinking of dominant perspectives. Keywords: inclusive development; epistemic injustice; islamic economic paradigm; structural injustice   Abstrak Pembangunan ekonomi inklusif merupakan amanat konstitusi untuk mewujudkan demokrasi ekonomi, keadilan sosial, dan kesejahteraan masyarakat. Namun, praktik pembangunan kerap dibatasi oleh struktur dan cara pandang dominan yang meminggirkan kelompok rentan. Artikel ini menganalisis ketidakadilan struktural dan epistemik dalam pembangunan inklusif di Indonesia melalui paradigma ekonomi Islam. Dengan pendekatan kualitatif-deskriptif dan analisis tematik terhadap dokumen kebijakan, teks hukum, dan literatur kritis, penelitian menunjukkan bahwa kebijakan pembangunan masih berorientasi pada kepentingan elite dan proyek berskala besar, serta mengabaikan suara kelompok rentan. Dengan mengintegrasikan nilai-nilai adl, maṣlaḥah, dan ta‘āwun, artikel ini menegaskan bahwa inklusivitas sejati menuntut reformasi kelembagaan, tata kelola partisipatif, serta peninjauan ulang cara berpikir dominan. Kata kunci: pembangunan inklusif; ketidakadilan epistemik; paradigma ekonomi islam; ketidakadilan struktural